A Case of Late Diagnosis of Anatomically Corrected Malposition of the Great Arteries - Hulitskyi, Bohdan I.; Raad, Tammo; Morkovkina, Hanna E.; Sydorova, Alyona V.; Maksymenko, Andrii V.; Stohova, Olena V.; Sekelyk, Roman I.; Yalynska, Tetiana A. (Ukrainian Journal of Cardiovascular Surgery, 2022)
Anatomically corrected malposition of the great arteries (ACMGA) is a rare form of congenital heart disease. This abnormality belongs to conotruncal anomalies. ACMGA is an anomaly in which aorta arises from the left ventricle and pulmonary artery arises from the right ventricle but great arteries are located in parallel relationships. Therefore, diagnosis of this disease is complicated due to frequent diagnostic errors. The aim. To share our experience of late diagnosis of ACMGA in a patientwho was previously mistakenly diagnosed with congenitally corrected transposition of great arteries (CC-TGA). Case report. We present a case of late diagnosis of ACMGA. An 11-day-old newborn was admitted to the Ukrainian Children’s Cardiac Center in 2007. After clinical examination, which included ultrasound examination, the diagnosis of CC-TGA, pulmonary stenosis, ventricular septal defect and atrial septal defect was conϐirmed. The patient was in a stable condition and there were no signs of heart failure. That is whythe patient was discharged. In 2017, cardiac catheterization was performed, and there were doubts about the diagnosis because of untypical anatomical features. In 2022, we performed computed tomography and magnetic resonance imaging. The diagnosis of ACMGA was made. Conclusions. ACMGA is an unusual form of congenital heart disease. The diagnosis of ACMGA is challenging, because its anatomical features are similar to those of CC-TGA. The difference of both these diagnoses is normal anatomy and hemodynamics but abnormal relationship in ACMGA, in contrast to abnormal anatomy in CC-TGA.